Whom God Wishes to Destroy . . . : Francis Coppola and the New Hollywood - Lewis, Jon, 1955- (Book collections on Project MUSE., 1995)
In March 1980 Francis Coppola purchased the dilapidated Hollywood General Studios facility with the hope and dream of creating a radically new kind of studio, one that would revolutionize filmmaking, challenge the established studio machinery, and, most importantly, allow him to make movies as he wished. With this event at the center of Whom God Wishes to Destroy, Jon Lewis offers a behind-the-scenes view of Coppola's struggle--that of the industry's best-known auteur--against the changing realities of the New Hollywood of the 1980s. Presenting a Hollywood history steeped in the trade news, rumor, and gossip that propel the industry, Lewis unfolds a lesson about power, ownership, and the role of the auteur in the American cinema. From before the success of The Godfather to the eventual triumph of Apocalypse Now, through the critical upheaval of the 1980s with movies like Rumble Fish, Hammett, Peggy Sue Got Married, to the 1990s and the making of Bram Stoker's Dracula and Kenneth Branagh's Frankenstein, Francis Coppola's career becomes the lens through which Lewis examines the nature of making movies and doing business in Hollywood today.